(untitled) (Research, Society and Development, 2024)
Euthanasia, although illegal in Brazil, is widely discussed in the legal field. In contrast, orthothanasia—death without suffering and at the right time—and dysthanasia—death with prolonged and painful life—are seldom discussed and remain unclear in legislation. This lack of discussion influences legislative decisions based on personal or corporate interests, neglecting human dignity. It is important to respect patient autonomy to ensure a dignified death and to criminalize dysthanasia. The objective of this article is to present a narrative review of the literature on dithanasia and orthothanasia, using the BVS and SciELO databases. Additionally, a critical analysis of Rui Nunes’s work “Ensaios em Bioética” was performed. Eightteen relevant articles were selected, along with analyses of the Constitution, Medical Ethics Code, and Civil and Penal Codes, to provide a comprehensive understanding of the legal, social, and ethical aspects. Technologies that allow for the artificial prolongation of patient life influence the practice of dysthanasia, which is condemned by the Brazilian Medical Ethics Code. Quaternary prevention aims to protect patients from excessive interventions. However, Brazilian legislation on the end of life is scarce and confusing, leading to the marginalization of orthothanasia and the practice of dysthanasia by doctors. Legislative proposals often do not differentiate between euthanasia and dysthanasia, being influenced by moral and religious dogmas that disregard patient dignity. Expanding the debate on death and creating clear legislation will ensure patient autonomy, which is essential for guaranteeing a dignified death with orthothanasia and avoiding dysthanasia.